Directed changes in the number of double-stranded RNA genomic segments in bacteriophage Φ6 - Onodera, Shiroh (The National Academy of Sciences, 1998)
Bacteriophage Φ6 has a genome of three segments of double-stranded RNA. The segments are designated S, M, and L. Each segment has a unique packaging site, pac, near the 5′ end of the plus strand. The plus strands of the segments are normally packaged in the order S, M, L. Chimeras of segment M and S in which segment M is at the 5′ end of the plus strand can be stably incorporated into the virion; however, an independent segment S must be included along with normal segment L, even if it contains no active genes. A chimera of segment M and S in which segment S is at the 5′ end of the plus strand can be stably incorporated into the virion along with normal segment L to form a two-segment genome. A chimera of segments S, M, and L in which the packaging sequence is that of S can also form a stable nonsegmented genome. These findings are consistent with a model that we have proposed for the packaging of the Φ6 genome.